POTENSI EKOWISATA BIRDWATCHING DI KETAMA ADVENTURE PARK MINAHASA - Novelianer M. Charvelindah; Wawan Nurmawan; Martina A. Langi (Universitas Sam Ratulangi, 2019)
ABSTRACT POTENTIAL OF BIRDWATCHING ECOWISATA IN KETAMA ADVENTURE PARK MINAHASA This research aims to study bird diversity and the effects of vegetation cover said dicersity, as well as perception of Touliang Oki villagers about Birdwatching Ecotourism in Ketama Adventure Park, Minahasa. The study was conducted in August to September 2019 in Ketama Adventure Park and Touliang Oki Village, Tondano District, Minahasa Regency. Observation were made using a point count method for bird diversity and vegetation cover, and rapid assessment and interviews for community perceptions. A total of 13 points were observed spread over 4 land cover types. This study found 48 bird species from 22 families. Shannon-Wiener Indeks calculation for diversity scores resulted in a value of 2.58, which falls into the medium category. Vegetation and habitat types were compared to each other to obtain similarity indices. This resulted in 6 pairwise comparisons, were 5 pairs had a high similarty index (> 50 %) while 1 pair had a low similarity indeks (< 50 %). Based on interviews Touliang Oki Villangers supports the existence of Birdwatching Ecotourism activities in Ketama Adventure Park as an economic driver. Keywords : Ecotourism, Birdwatching, Ketama Adventure Park.